Vishaghn Dhoop, Nano-Scale Particles with Detoxifying Medicinal Fume, Exhibits Robust Anti-Microbial Activities: Implications of Disinfection Potentials of a Traditional Ayurvedic Air Sterilization Technique - Acharya Balkrishna DLitt; Swami Yagyadev MA; Swami Vipradev MA; Kanchan Singh MSc; Yash Varshney MSc; Shubhangi Rastogi PhD; Swati Haldar PhD; Anurag Varshney PhD (SAGE Publishing, 2022)
The rapidly increasing global burden of healthcare associated infections (HAI) is resulting in proportionate increase in chemical disinfection in healthcare settings, adding an extra burden of environmental toxicity. Therefore, alternative disinfection techniques with less or no adverse side-effects need to be explored. In this regard, ayurvedic ' dhoopan ' technique involving slow combustion of medicinal herbs, minerals and animal products hold great promise. In this study, dhoopan of a traditionally defined ayurvedic medicinal mix, 'Vishaghn Dhoop' (VD) has been assessed for its anti-microbial potentials against both Gram-positive and negative pathogenic bacteria, Mycobacterium and pathogenic fungus, Candida albicans . Fume generated from slow combustion of VD was subjected to physico-chemical characterization and was assessed for anti-microbial effects. VD fume contained particles of 354 ± 84 nm size, laden with anti-microbial metabolites. On agar plates, VD fumigation reduced bacterial growth by 13 - 38%. Liquid culture aeration with VD fume inhibited bacterial growth by 50 - 85%, and fungal growth by 80%. In real life settings (in vivo) , un-sanitized rooms fumigated with VD fumes for 30 min reduced the environmental microbial loads by 10 folds. In addition, the safety of VD fumigation was evaluated through in vitro cytotoxicity assay on human lung epithelial (A549) cells. Cells exposed to media-collected VD fumes for 24 h exhibited normal cyto-safety profile. Collectively, these observations provide scientific evidence in support of a traditional technique of disinfection, which can be fine-tuned to have implications in clinical, healthcare and food industry where, disinfection is a prime requirement.